Morocco : Third Review Under the Arrangement Under the Precautionary and Liquidity Line (PLL)-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Morocco's Third Review Under the Arrangement Under the Precautionary and Liquidity Line (PLL). Morocco's economic fundamentals and policy frameworks are sound, the country is implementing generally sound policies, and remains committed to maintaining such policies in the future. End-September 2017 quantitative indicative targets on the fiscal deficit and international reserves were met. The authorities have not drawn on the arrangement and continue to treat it as precautionary. Morocco also meets the PLL qualification criteria, performs strongly in three out of the five PLL qualification areas (monetary, financial, and data), and does not substantially underperform in the fiscal policy, and external position and market access areas.